Corrosion of Al(Co)CrFeNi High-Entropy Alloys - Godlewska, Elżbieta M.; Mitoraj-Królikowska, Marzena; Czerski, Jakub; Jawańska, Monika; Gein, Sergej; Hecht, Ulrike (Frontiers in Materials, 2020)
High entropy alloys: AlCrFe2Ni2Mox (x = 0.00, 0.05, 0.10, 0.15), AlCoCrFeNi and two quinary alloys with compositions close to its face centered cubic (FCC) and body centered cubic (BCC) component phases, are tested for corrosion resistance in 3.5 wt. % NaCl. The materials with different microstructure produced by arc melting or ingot metallurgy are evaluated by several electrochemical techniques: measurements of open circuit voltage (OCV), cyclic potentiodynamic polarization, and electrochemical impedance spectroscopy (EIS). Microstructure, surface topography and composition are systematically characterized by scanning electron microscopy (SEM) and energy dispersive x-ray spectroscopy (EDS). The results indicate that minor additions of Mo positively affects corrosion resistance of the AlCrFe2Ni2 alloy by hampering pit formation. The FCC phase in the equimolar alloy, AlCoCrFeNi, is proved to exhibit more noble corrosion potential and pitting potential, lower corrosion current density, and corrosion rate compared with the BCC phase. Overall behavior of the investigated alloys is influenced by the manufacturing conditions, exact chemical composition, distribution of phases and occurrence of physical defects on the surface.